KEBIJAKAN ASURANSI KESEHATAN UNTUK RAKYAT MISKIN (ASKESKIN): HARAPAN DAN KENYATAAN IMPLEMENTASI - Damayanti, Kania (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
Health Insurance for Poor People (Akseskin) policy implementation as mandated by the national constitution UUD 1945 have encountered shortcoming s with its policy substances, health services, technical operation, and beneficiaries. Its uncompleted implementation regulation as authorized in Law No. 40 Year 2004 may have contributed to the problems. The completetion of Akseskin policyand implementation substances may be conducted in relation with the contexts of regional autonomy, nation-wide social security program, and poverty alleviation program. It also requires the implementation of good governance, central and local gogernment regulations, quality service standards, authorization of responsibilities, monitoring, continuous evaluation and the availability of Akseskin management information system. Akseskin policy arrangement, in its initial stage, entails revisions especially in the terms of resource management, executing organization unit, mechanism and procedures.